Capital Flow in Contemporary Global Economy - Ewa Kopeć (Contemporary Economics)
The purpose of this publication is a capital flow analysis of six selected countries that cause a growth of world-wide imbalance. The comparison of the balance of payments between 1999 and 2008 in the USA, Japan and the BRIC countries gives information about the scale and the rate of the economic growth. The publication consists of four parts. Initially, the structure of the balance of payments was characterized, giving a general view on all economic transactions in each country and the influence of the capital traffic on it. Subsequently, reasons and the scale of the growth of the world-wide imbalance were characterized. Finally, selected components of the balance of payments were discussed on the basis of data publicized by the International Monetary Fund.